Association Of Iron Deficiency Anaemia With Preterm Birth: A Cohort Study At Dhq Hospital Sargodha - Iram, Samia; Abbas, Afroza; Sarfraz, Nazish; Shaheen, Sadaf; Ashiq, Zoobia; Zafar, Rida (Journal of Rawalpindi Medical College, 2025)
Objectives: IDA is a major health concern for pregnant women throughout the world, mainly attributable to differences in socioeconomic and geographical status. This study investigates the association between IDA in pregnant women and the incidence of preterm births. Materials and methods: This cross-sectional, consecutive cohort study was performed in the Gynaecology and Obstetrics department at DHQ Hospital, Sargodha, from August 16, 2020, to January 5, 2021 and included 60 pregnant women with an exposure (IDA) and 60 pregnant women with normal hemoglobin values. Demographic variables for age, gestational age at presentation, and maternal weight were similar across the groups. Results: In the various groups, the results indicated that the IDA group exhibited a significantly higher prevalence of preterm births of 43.3% compared to the control group with only 20%, and a relative risk estimate of 2.2 and a p-value of 0.052, suggesting the results were near or at statistical significance. Methods of stratification indicated that low weight of the mother was statistically associated with increasing risk of prematurity within the IDA group. It seems that early intervention in cases of IDA during pregnancy is crucial to have a reduced rate of neonatal complications. Conclusion: Hence, this study adds to the literature the relationship between maternal iron status and preterm birth, with an appeal to improve pre-antenatal care practices that incorporate initial assessment and correct supplementation of iron.